Evaluating the Methodological Quality of Postexercise Hypotension Aerobic Exercise Interventions - Day, Christina; Wu, Yin; Pescatello, Linda S. (Frontiers in Physiology, 2022)
Background: Postexercise hypotension (PEH) is the immediate reduction in blood pressure (BP) of 5-8 mmHg that occurs after a single bout of aerobic exercise among adults with hypertension. Across PEH studies there are variations in the level of rigor of the study designs and methods that limit the conclusions that can be made about PEH. Objective: To develop and then apply a methodological study quality evaluation checklist to aerobic exercise PEH studies to provide methodological guidance. Methods: We developed a PEH checklist (PEH√list) based upon contemporary methodological study quality standards. The PEH√list contains 36 items divided into three categories: sample (n=10 items), study (n=23 items), and intervention characteristics (n=3 items). We then systematically searched six databases to January 2019 to identify and then evaluate studies that: 1) enrolled adults > 18yr with hypertension and without other chronic diseases or conditions; 2) included a bout of aerobic exercise and a non-exercise control session; and 3) were published in English. Results: Of 17,149 potential studies, 64 qualified. Participants (N=1,489) were middle-aged (38.6±15.6yr), overweight (26.1±2.5kg/m2) mostly men (64.4%) with elevated BP (systolic BP 129.5±15.2 / diastolic BP 81.0±10.1mmHg). Overall, the qualifying studies satisfactorily reported 61.1%±12.6% (32.3% to 85.2%) of the relevant items on the PEH√list. Of note, only 20.3% of the studies disclosed BP was measured following professional guidelines, 18.8% reported BP was taken by the same assessor pre- and post-intervention, and 35.5% stated participants abstained from caffeine, alcohol, and physical activity prior to testing. Half (51.5%) indicated they statistically controlled for pre-exercise/baseline BP. Meanwhile, 100% of the studies reported the setting in which the BP measurements were taken, time from the end of exercise to the start of the BP measurements, and if relevant, the length of the ambulatory BP monitoring period. Conclusions: Overall, the PEH√list items were not well satisfied; especially items with potential confounding effects on PEH. We contend the PEH√list provides guidance to investigators on the important methodological study considerations in PEH aerobic exercise studies that should be attended to in future.